Knowledge and Perception of Healthcare Professionals about the Need for Radiopharmacists in Hospitals in the Philippines - Ramil, Rhian Jaymar; Ines-Ramil, Ma Danica; Viado-Rojas, Janelyn; Bautista, Learni Magdalena (Journal of Pharmacy Practice and Community Medicine)
Background: In most Asian countries, nuclear pharmacy practice is not an emerging specialty area. Radiopharmacy is considered to be a dearth career in the Philippines. This study attempts to explore on the need for radiopharmacists in the Philippines by assessing initially the knowledge and perception of healthcare professionals working in hospitals. Materials and Methods: A cross-sectional survey using a self-administered questionnaire was employed to 165 respondents in Ilocos Norte and Ilocos Sur. Data were recorded and analyzed using the SPSS 20. Results: On the whole, results showed that most respondents were aware about radiopharmaceuticals. Moreover, healthcare professionals strongly agreed that radiopharmacists are needed in the country. And, patient safety was on the top priority as strongly agreed by the healthcare professionals. Conclusion: Respondents regarded that radiopharmacists are accepted and needed in the Philippines. The role of radiopharmacists complements with other healthcare professionals in optimizing proper use of radiopharmaceuticals towards quality patient health outcomes and patient safety.
Keywords: Radiopharmacist; Nuclear pharmacy; Radiopharmaceuticals; Patient safety; Healthcare professionals; Hospitals